Prevalence of thalassaemia among childbearing-age Li and Han populations in Hainan Province - Fangchao Tao; Yanquan Lai; Jiaqi Chen; Shijie Wei; Yu Zou; Yunli Lai; Qiongzhen Qin; Yufeng Wang; Wanjun Zhou (Hematology)
Objectives Accurate epidemiological data are crucial for effective disease prevention and treatment. We conducted a large-scale survey to explore the thalassaemia prevalence and spectrum among the two major ethnic groups in Hainan Province.Methods A total of 399,053 childbearing-age individuals of Li (n = 77,563) and Han(n = 321,490) ethnic groups were recruited from 18 cities and counties in Hainan, and their thalassemia genotypes were systematically screened and statistically analysed.Results This study revealed a significantly higher thalassaemia carrier rate in the Li (55.39%) than that in the Han (13.13%). Specifically, the carrier rate of α-thalassaemia was 46.39% in the Li and 10.02% in the Han. The predominant α-thalassaemia mutations were – α3.7 and – α42. in Li, whereas the main mutation were – SEA and – α4.2 in Han. For β-thalassaemia, the carrier rates were 1.68% in Li and 2.38% in Han, with CD41-42(-CTTT) the most prevalent mutation in both groups. The carrier rates of β-/α-compound thalassaemia were 7.32% in Li and 0.73% in Han. Additionally, there were regional differences in the distribution of thalassemia among the Li and Han within Hainan Province.Conclusion Epidemiological characteristics and molecular spectrum of thalassaemia among the Li and Han ethnic groups in Hainan were revealed in this study. These findings can provide a scientific basis to develop and implement prevention strategies for thalassaemia in Hainan.